Economic Opportunities and Gender Equity: The Migration and Education Decisions of Young Women from Rural China - Chunbing Xing; Yan Sun (Institute of Labor Economics (IZA), 2019)
We study how the migration decision of young women in rural China is shaped by the return arrangement and opportunities of college education. Women outnumbered men in young rural-urban migrants in the early 2000s, but the surplus of young women has recently disappeared. We propose that the temporary nature of migration and an earlier return time relative to men are the major reasons that women migrate at a younger age. When higher education expansion increased women's chance of permanent migration, women stayed in school longer. Empirical evidence is consistent with this hypothesis. Marriage motives and demand factors are also considered.
Keywords: J12; J16; O15; R23; 330; migration; gender; education expansion; marriage